2015
DOI: 10.1002/jrs.4771
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of silver nanocolloids in the Langmuir–Blodgett Film of stearic acid: Evidence of an efficient SERS sensing platform

Abstract: Highly sensitive surface-enhanced Raman scattering active substrate obtained by self-assembly of silver nanocolloids (AgNCs) in the bilayer Langmuir-Blodgett (LB) film of stearic acid (SA) has been reported. Rhodamine 6G (R6G) has been used as the probe molecule to test the efficacy of the as prepared substrate. Gigantic enhancement factors~10 12 orders of magnitude have been estimated from the surface-enhanced resonance Raman scattering [SER(R) S] spectrum of R6G, which proves that the as prepared substrate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Saha and co‐workers studied self‐assembly of silver nanocolloids in the Langmuir–Blodgett Film of stearic acid as evidence for an efficient SERS sensing platform. They find gigantic enhancement factors (∼10 12 ) have been estimated from the SERS [SER(R)S] spectrum of R6G, which proves that the prepared substrate is superior or comparable with silver nanoparticle as dried AgNC solutions on microscopic slides . Saxena and co‐workers have used Raman spectroscopy to study the interplay between phonon confinement and the Fano effect in silicon nanowires.…”
Section: Nanomaterialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Saha and co‐workers studied self‐assembly of silver nanocolloids in the Langmuir–Blodgett Film of stearic acid as evidence for an efficient SERS sensing platform. They find gigantic enhancement factors (∼10 12 ) have been estimated from the SERS [SER(R)S] spectrum of R6G, which proves that the prepared substrate is superior or comparable with silver nanoparticle as dried AgNC solutions on microscopic slides . Saxena and co‐workers have used Raman spectroscopy to study the interplay between phonon confinement and the Fano effect in silicon nanowires.…”
Section: Nanomaterialsmentioning
confidence: 98%
“…They find gigantic enhancement factors (∼10 12 ) have been estimated from the SERS [SER(R)S] spectrum of R6G, which proves that the prepared substrate is superior or comparable with silver nanoparticle as dried AgNC solutions on microscopic slides. [84] Saxena and co-workers have used Raman spectroscopy to study the interplay between phonon confinement and the Fano effect in silicon nanowires. They concluded that such an interplay can be represented by considering a general Fano-Raman line-shape equation to represent the combined effects in SiNWs.…”
Section: Cells Bacteria and Virusesmentioning
confidence: 99%
“…In the practical application, silver nanoparticles are coated on the substrate, which is known as SERS substrate. Mostly, researchers start to prepare good colloidal silver nanoparticles and then to deposite them on a certain substrate using spin coating technique [8], Langmuir Blodgett technique [9], drop dry technique [2], block copolymer process [10] and printing technique [11] which are known quite complicated. Furthermore, the silver nanoparticles are sometimes not easily to deposit on the substrate, thus the silver nanoparticles disappear when the substrate is immersed in liquid sample or analyte.…”
Section: Introductionmentioning
confidence: 99%
“…Methods that have been used to produce AgNPs include chemical methods [21], electrochemistry [22], radiation [23], photochemical methods [24], Langmuir-Blodgett [25], and phytochemicals-based approaches [26]. The use of chemical methods involves toxic chemicals, such as reducing agents and capping agents that are not safe for the environment.…”
Section: ■ Introductionmentioning
confidence: 99%